The determinants of length of stay of tourists in the Azores - Menezes, António Gomes de (2008)
This paper examines the determinants of the length of stay of tourists in the Azores. It is found that socio-demographic profiles, such as nationality and Azorean ascendancy, and trip attributes, such as repeat visitation rates and type of flight, are important determinants. In addition, destination image and attitudes regarding environmental initiatives, constructed from a factor analysis exercise, also influence the length of stay. In particular, the results suggest that marketing strategies which promote the Azores for its nature, landscape, remoteness and weather may increase length of stay, whereas cultural heritage has the opposite effect.